Intraocular pressure as indicator of sympathetic asymmetry in the eyes - Reddy, Sagili Chandrasekhara (International Journal of Ophthalmology Press, 2010)
AIM: To determine the asymmetry in the sympathetic activity in the eyes as indicated by intraocular pressure (IOP). METHODS: In a prospective cross sectional study, the IOP in 150 newborns, 80 young adults and 159 old people was measured with Tono-Pen under topical anaesthesia. RESULTS: The mean IOP in the newborns was 16.16mmHg in right eye and 15.79mmHg in left eye; in young adults 15.04mmHg in right eye and 14.71 in left eye; in old people 15.16 in right eye and 15.03 in left eye. A statistically significant higher IOP was noted in the right eye in the newborns (P=0.03) and in young adults (P=0.02), but not in the old people (P=0.26). The higher IOP in the right eye indicates the lowered sympathetic activity in that eye. CONCLUSION: We hypothesize that the sympathetic asymmetry in the bilaterally placed organs helps to establish the dominant pattern of the organ in the body.